Пожалуйста решите тождества: а)(a-1)^3-4(a-1)=(a-1)(a+1)(a-3); б)(x^2+1)^2-4x^2=(x-1)^2(x+1)^2

1

Ответы и объяснения

2013-05-07T10:48:12+00:00

а) (a-1)^3-4(a-1)=(a-1)(a+1)(a-3)

a^3-3a^2+3a-1-4a+4-(a-1)*(a+1)*(a-3)=0

a^3-3a^2-a-1+4-(a-1)*(a+1)*(a-3)=0

-3a^2-a+3+3a^2+a-3=0

-a+3+a-3=0

3-3=0

0=0

Тождество доказано! 

 

б) (x^2+1)^2-4x^2=(x-1)^2(x+1)^2

x^4-2x^2+1-(x^2-2x+1)*(x+1)^2=0

x^4-2x^2+1-(x^4-2x^2+1)=0

x^4-2x^2+1-x^4+2x^2-1=0

-2x^2+1+2x^2-1=0

1-1=0

0=0

 

Тождество доказано!